Effects of a cognitive-behavioral intervention program on the health of caregiversof people with autism spectrum disorder - Nicolás Ruiz-Robledillo; Luis Moya-Albiol (Psychosocial Intervention, 2015)
Caregivers of people with autism spectrum disorder (ASD) are chronically exposed to high levels of stress.In turn, such stress is associated with high rates of negative health outcomes. However, few studies haveanalyzed the effects of psychotherapeutic interventions in improving health in this population. The mainaim of the present study was to evaluate the effectiveness of a cognitive-behavioral intervention program,based on the model proposed by Ruiz-Robledillo and Moya-Albiol (2014a). For this, we used a sample of 17informal caregivers of people diagnosed with ASD. The study was based on a pre-post design. Caregivershad lower levels of burden immediately after the intervention than at baseline, while both immediatelyafter the intervention and at 1 month of follow-up, they had fewer somatic symptoms, lower levels ofdepression, and better mood states than at baseline. These results provide evidence of the efficacy of thecognitive-behavioral intervention developed for reducing stress and health complaints in chronicallystressed caregivers. Additionally, the program could be useful in early stages of the caring process, toprovide caregivers with effective skills for preventing future health problems. The integration of theprogram in general psychosocial interventions would be highly beneficial for this population.